Impact of the Marie Curie Cancer Care Delivering Choice Programme in Somerset and North Somerset on place of death and hospital usage: a retrospective cohort study. Issue 1 (16th May 2014) - Purdy, Sarah; Lasseter, Gemma; Griffin, Thomas; Wye, Lesley
Abstract : Objectives: The Marie Curie Cancer Care Delivering Choice Programme (DCP) aims to help palliative patients be cared for in their place of choice. In this study, new palliative care services delivered in two counties in England included end-of-life care coordination centres, an out-of-hours telephone line and discharge in-reach nurses. The study aimed to investigate the impact of DCP on place of death and hospital usage (emergency department (ED) and admissions). Methods: Retrospective cohort of all eligible palliative patients who died over a 6-month period in two counties (n=3594). Participants were those who died of conditions considered to be eligible for end-of-life care, as defined by the Public Health England National End of Life Care Intelligence Network. The sample included people who did and did not access DCP services. DCP service, hospital admission and ED use data, demographic and death data were collected on all eligible participants. Data were analysed using descriptive statistics and logistic regression. Results: After adjusting for potential confounders, those using Delivering Choice were at least 30% less likely to die in hospital or have an emergency hospital admission or ED visit in the last 30 or 7 days of life than those who did not. Conclusions: Recipients of DCP services were less likely to die in or use hospital services. Those considering new ways of providing end-of-life care could explore the possibility of adopting similar services and evaluating the outcomes from patient, carer and system perspectives.